1992
DOI: 10.1016/0024-3205(92)90519-u
|View full text |Cite
|
Sign up to set email alerts
|

Endothelin-3 like immunoreactivity in plasma of patients with cirrhosis of the liver

Abstract: SummaryA highly specific and sensitive radioimmunoassay (R/A) has been established for determination of endothelin-3 like immunoreactivity in human plasma to investigate its possible role in hemodynamic alterations due to liver disease. Crossreactivity with other endothelin isoforms was always below 4 %, the lower detection limit following extraction on Sep-Pak C18 cartridges was 0.5 pg/ml. The concentration of endothelin-3 (mean + SEM) was 4.16 + 0.56 pg/ml (n = 13) in plasma of patients with cirrhosis of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
2
2

Year Published

1995
1995
2005
2005

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 35 publications
(16 citation statements)
references
References 12 publications
0
12
2
2
Order By: Relevance
“…Previous studies are conflicting. There are papers reporting that cirrhotic patients have significantly higher levels of ETs and this increase is mostly due to an increase in ET‐1 and ET‐3 in some cases in proportion to the severity of liver damage 27–33 . By contrast, other studies report that this difference is not significant 31, 34 in patients without ascites.…”
Section: Discussionmentioning
confidence: 98%
“…Previous studies are conflicting. There are papers reporting that cirrhotic patients have significantly higher levels of ETs and this increase is mostly due to an increase in ET‐1 and ET‐3 in some cases in proportion to the severity of liver damage 27–33 . By contrast, other studies report that this difference is not significant 31, 34 in patients without ascites.…”
Section: Discussionmentioning
confidence: 98%
“…[6][7][8] In the largest and most detailed study, it was observed that circulating ET-1 and ET-3 concentrations were increased in patients with severe liver disease, with a more marked increase in plasma ET-1 concentrations in patients with HRS due to alcoholic hepatitis or acute liver failure (type 1 HRS). 8 9 Eight years on it was shown that the high plasma ET-1 levels in patients with HRS decreased rapidly within one week after orthotopic liver transplantation, and this was followed by an improvement in renal function.…”
Section: Hepatorenal Syndromementioning
confidence: 99%
“…In patients with cirrhosis of the liver elevated arterial and venous plasma concentrations of ET-1 and ET-3 have been described [2,[10][11][12][13][14][15][16]. Interestingly, there is an increased hepatosplanchnic release of ET in these patients.…”
Section: Et Plasma Concentration and Hepatic Release In Cirrhosismentioning
confidence: 99%